(untitled) (Global Journal of Human-Social Science, 2019)
Some things at a glance though not desirable could be tolerated and ignored in this 21st century regarding the outlook of a typical classroom but not a naked classroom. The paradigm shift in the age of the technology driven instructional delivery is a classroom equipped with modern technological tools for enhancing teaching and learning. The new age schools and educational institutions pride themselves as having learning delivered by state-of-the-art technology thus classrooms having the touch of information and communication technology equipment and teachers who are trained in the art, students as digital natives etc. Anyone who thinks otherwise (stripping classroom naked) must be living in the past would be the immediate response to such postulation. This paper take a critical look at a naked classroom, in bid to unravel whether so doing has any relevance; a technique or a fallacy. The paper makes conclusion and recommendations amongst others that our classrooms should be reserved for useful face-to-face discussions and engaging students by using technology outside the classroom.